Stimulasi Puting Susu terhadap Lama Pengeluaran Plasenta - Rasyid, Hernita Sutiawati (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2020)
Bleeding is still the second highest cause of AKI in Gorontalo Province. Bleeding in the mother after delivery can be caused by retained placenta, which is a condition where the placenta has not been born 30 minutes after the fetus is born. Nipple stimulation carried out immediately after the baby is born can influence the hypothalamus to release the hormone oxytocin which will strengthen uterine contractions thereby shortening the time for placental separation.Objective: To analyze the effect of nipple stimulation on the duration of expulsion of the placenta.This research method uses Pre Experiment Design research with Static Group Comparison. The k population used was 30 mothers who gave birth normally, consisting of 15 respondents in the nipple stimulation intervention group and 15 respondents in the control group. Independent variable; nipple stimulation and the dependent variable of the duration of expulsion of the placenta.Results: The average length of time for expulsion of the placenta in the nipple stimulation intervention group was 7.07 minutes and the control group mother was 11.13 minutes. The results of statistical tests with Independent t-test = 0.004 < 0.05.The conclusion is that there is an effect of nipple stimulation on the duration of expulsion of the placenta.